ANALISIS KESESUAIAN BIAYA RIIL DENGAN TARIF INA-CBG’s PASIEN HIPERTENSI RAWAT INAP DI RSUD MITRA SEHAT : Indonesia - Tatilu, Joice Ester; Ruindungan, Putrinesia Kinanti; Manawan, Fridly (Sam Ratulangi University, 2025)
Despite the government's intensified efforts to implement budget efficiency, Indonesia still faces challenges with the deficit in social security spending for healthcare management. Hypertension is one of the cardiovascular diseases that can lead to complications such as kidney failure, stroke, and coronary heart disease, which can create a domino effect, further inflating the treatment costs for patients. This study aims to determine the magnitude of the difference between actual costs and the INA-CBG’s tariff for inpatient hypertension patients at RSUD MITRA Sehat. This study is an analytical observational study using a cross-sectional approach with purposive sampling. Data on inpatient hypertension patients were obtained retrospectively from the medical records and BPJS claims department of RSUD MITRA Sehat. A total of 42 patients met the inclusion and exclusion criteria and became the study sample. There was a difference of Rp 1,925,000 between the actual costs and the INA-CBG tariff.